Use of anabolic steroids by gymgoers: Reasons and perspectives (Research, Society and Development, 2021)
Introduction: The media, the gym and the practice of bodybuilding are contributing factors to the influence of the search for a perfect body in the young population. With the popularization of social networks, fitness muses, bloggers and models are great incentives for the consumption and sale of supplements, vitamins and anabolics, without any scientific evidence or recommendation from a health professional. Objective: in this research, carried out with gym goers, we sought to analyze the relationship between motivation and expectation of the use of anabolic steroids and aging. Methods: Research of an applied and exploratory nature, with a qualitative approach, using a semi-structured interview as a procedure for data collection. Individuals using male anabolic steroids were evaluated. The data were extracted through content analysis. Results: 18 male individuals participated in the research, with an average age of 28 years; 72% are single; the majority with graduation and family income varying from 4 to 10 thousand reais. As for the use of steroids, the data showed that their use goes, initially, from aesthetics to a use of a psychological nature, as it helps them to overcome past traumas. We consider this to be the reason why individuals did not relate the use to future consequences (aging) but as partly personal satisfaction. Conclusion: Individuals seek the gym due to the fact of problems with acceptance of the body in childhood or adolescence, seeking quick results to be better seen in society.